Intestinal endometriosis: a diagnostic dilemma - Juneja, Sunil Kumar; Virk, Satpal Singh; Singla, Saurabh; Sachdeva, Kamal; Kaur, Harpreet; Sharma, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Endometriosis is a benign gynaecological condition that causes significant morbidity to women of reproductive age group. It uncommonly affects the gastrointestinal tract and acute bowel obstruction is a rare manifestation. Methods: A retrospective observational study was conducted on eight patients. Results: In three patients (37.5%), small intestinal involvement was seen, and colon was involved in five patients (62.5%). One (12.5%) patient presented with complete bowel obstruction while in others partial obstruction of the intestine was seen. Conclusions: Intestinal endometriosis is a diagnostic challenge and should be considered in young menstruating women with gastrointestinal symptoms. Intestinal endometriosis is the most common extra-pelvic site and it is found in 12% of women with endometriosis. The true incidence of endometriosis causing bowel obstruction is unknown. Pre or intraoperative sigmoidoscopy may prove helpful in ruling out malignancy. The gold standard for diagnosis is laparoscopy and biopsy, which allows a full assessment of the pelvis as well as surgical resection if required. The management of endometriosis is an integrated approach of both medical and surgical therapy. Bowel resection is usually undertaken if there are features of obstruction or bleeding, and if there is suspicion of malignancy.